PENGARUH EDUKASI DENGAN MEDIA SOSIAL INSTAGRAM DAN YOUTUBE TERHADAP PENGETAHUAN GIZI SEIMBANG PADA SISWA SMA NEGERI 1 CIKARANG UTARA - Dinda Latifa Rinarto (2021)
Education with social media on Instagram and YouTube is an interesting preventive way for teenagers, especially in improving nutritional knowledge. Increased knowledge about nutrition can influence attitudes and behavior in the selection of nutritionally balanced food ingredients, so that indirectly will affect the nutritional status of adolescents. This research was conducted to find out the influence of Instagram and YouTube social media on balanced nutrition knowledge in students of SMA Negeri 1 Cikarang Utara. This type of research is Quasi-experiment, with one group pretest-posttest design. The respondents were 52 students, 11th graders (26 students, Instagram groups; 26 students, YouTube groups) and were intervened through Instagram posts and YouTube videos twice each in one week and repeated for four weeks. The results of this study showed that there is an influence of nutrition education with Instagram social media on knowledge (p= 0.000) and there is an influence of nutrition education with YouTube social media on knowledge (p= 0.010). Then, providing nutrition education with Instagram can affect knowledge by (41.9%) and with YouTube (24.3%).